Analyzing the Feminism Consciousness in the Novel of Manju Kapur: Exploring Women's Issues in Manju Kapur's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Manju Kapur is the prominent ladies author in the field of Indian writing. She is considered to be the most splendid star of Indian ladies essayist of English. She is the developing figure in the field of writing, who has essentially contributed her work in Indian fiction. In the entirety of her works she manages the issue of ladies languishing. The principle undertaking of the women's activist literary pundits appears to stand guard against the checking man centric standards which have been inhered ceaselessly. The minimizations of ladies, their scrape, struggle for identity, finding their own space, praising the female body are the main subjects of this pattern. This article endeavors at looking at the socio-cultural evolution of ladies after some time in India and where they stand now as delineated in Manju Kapur's novels.